Career-Decision Making: School Counselors in Counselor Education Doctoral Programs - Malti Tuttle; Lee E. Grimes; Caroline Lopez-Perry (Teaching and Supervision in Counseling, 2019)
School counselors enroll in counselor education doctoral programs based on various factors which impact their future career-decision making process. The researchers conducted a phenomenological research study to examine the career-decision making experiences of practicing school counselors in counselor education doctoral programs to understand this phenomenon. Ten practicing school counselors enrolled in counselor education doctoral programs participated in this research study. Three emerging themes highlighted the essence of these experiences: (a) intrinsic and extrinsic motivators, (b) developmental fit, and (c) lifestyle factors. Results and recommendations from this research study provide counselor educators insight into these experiences. This research study informs counselor educators about these experiences and provide an understanding for the need to support and guide school counselors in counselor education doctoral programs through teaching.
Keywords: counselor education doctoral programs; school counselors; career-decision making; teaching; phenomenological research